Perbandingan Terapi Injeksi Steroid dan Terapi Bedah Dekompresi Dengan Endoskopi Dalam Pengobatan Carpal Tunnel Syndrome - Clara Angelica Rotoro (Populer: Jurnal Penelitian Mahasiswa, 2023)
Carpal tunnel syndrome (CTS) is a condition that causes pain, tingling and weakness in the hand due to compression of the median nerve in the wrist. Treatment of CTS is based on two main approaches, namely steroid injection therapy and endoscopic surgical decompression therapy. Steroid injection therapy provides greater temporary pain relief, but the benefits are not permanent. At the same time, surgical decompression treatment with endoscopy is a definitive treatment that is more effective in the long term and has a lower therapeutic failure rate than steroid injection treatment. This literature research explores various scientific studies and related literature that have been conducted in recent decades to understand the effectiveness and relative superiority of these two treatment methods. This review covers clinical aspects, such as the rate of pain recovery, recovery of hand function, as well as the impact on the patient's quality of life. The results of this literature review indicate that both treatment methods have their respective advantages and disadvantages. Steroid injection therapy can provide rapid and minimally invasive symptom relief, while endoscopic surgical decompression therapy tends to provide more lasting and complete improvement. Factors such as symptom severity, patient preference, and medical recommendations may influence the choice between these two methods.